West African Contribution to the Law of International Watercourses - Rowny, K. (Obafemi Awolowo University Press, 2013)
The idea of the non-navigational uses of international watercourses has been mooted in international treaties and in the doctrine of international law. This issue arises because water flowing from one country to another has been used in increasing degrees for irrigation of arid areas, for generation of electricity and generally for the development of industry. With these new developments new problems have arisen for lawyers to solve. In the case of irrigation, the uses of water by upper riparians inevitably diminish its natural quantity in the lower part of the river and thus adversely affect the lower riparians. Although hydrologic works for power purposes do not consume water as such, they interfere with its normal flow and produce the same consequences for the lower riparians as in the above case. Furthermore, increasing industrialization entails more consumption of water and changes in its natural quality giving rise to water pollution, detrimental to biological life (fauna and flora) and thus adversely affects the consumers of water, human beings, animals and plants alike.